Discussion on techniques of data cleaning, user identification, and session identification phases of web usage mining from 2000 to 2022 - Mohammed Ali Mohammed; Hala Abdulsalam jasim; Ahmed Oday (Iraqi Journal for Computers and Informatics)
The data preprocessing step is an important step in web usage mining because of the nature of log data, which are heterogeneous, unstructured, and noisy. Given the scalability and efficiency of algorithms in pattern discovery, a preprocessing step must be applied. In this study, the sequential methodologies utilized in the preprocessing of data from web server logs, with an emphasis on sub-phases, such as session identification, user identification, and data cleansing, are comprehensively evaluated and meticulously examined.